Globalizing Responsibility : the Political Rationalities of Ethical Consumption. - Barnett, Clive (RGS-IBG book series., 2010)
Globalizing Responsibility: The Political Rationalities of Ethical Consumption presents an innovative reinterpretation of the forces that have shaped the remarkable growth of ethical consumption.: Develops a theoretically informed new approach to shape our understanding of the pragmatic nature of ethical action in consumption processes; Provides empirical research on everyday consumers, social networks, and campaigns; Fills a gap in research on the topic with its distinctive focus on fair trade consumption; Locates ethical consumption within a range of social theoretical debates -on neoliberal.